PENGARUH PELATIHAN BEBAN KETTLER TERHADAP KEMAMPUAN TENDANGAN DOOLYO CHAGI ATLET TAEKWONDO PUTRA SMA ANTARTIKA SIDOARJO - Fazdinata, Jerry Anatoly (Jurnal Kesehatan Olahraga, 2018)
ABSTRACT The aim of this research is knowing there is the influence of Kettler load training on ability Doolyo Chagi atlet Taekwondo putra SMA Antartika Sidoarjo. This research a quasy experiment with approach the quantitatif of Pre Experimental Design and Pretest ? Treatment ? Posttest method and to measure ability of Doolyo Chagi use Body Protector Scoring Sytem / Point Scoring System (BPSS/PSS). The sample of this research 15 atlet putra Taekwondo SMA Amtartika Sidoarjo.Technical analysis of data use manual system microsft exel 2010 and SPSS application. And based on the results calculations obtained, result of influence of Kettler load training on ability Doolyo Chagi atlet for left leg has an average 37 times kick / 60 second, while the results of influence of Kettler load training on ability Doolyo Chagi atlet for right leg has ana average 39 tmes kick / 60 second. Hypothesis testing use wilcoxon testing with a significant level (n) = 0,05 then obtained wilcoxon test amount -3,4 dan amount -1,9 then rejected dan be accepeted. Because the value -3,4 greater than -1,9. From the results of the reseach taken can be concluded that Kettler's load training has influenced the kicking ability of Doolyo Chagi athlete Taekwondo son of SMA Antartika Sidoarjo. Key Words: Taekwondo, load Kettler, Doolyo Chagi